Analisis Studi Kelayakan Bisnis Penyewaan Lapangan Futsal Centro Kajen - Muhammad Azka Fajar Mufarih; M. Taufiq Abadi (Jurnal Riset Akuntansi, 2023)
This article discusses business feasibility in the service sector in the field of leasing a futsal field located in Gejlig Village, Kajen District, Pekalongan Regency. Being in a strategic location makes the centro futsal field rental quite attractive to the local community. The business development in the futsal field rental sector has been very rapid, seen from the fans of this sport, it has made business people see the opportunities that exist to be used as a productive business. The research method used in this article is a qualitative method. Data collection in this method is by interviewing one of the sources who work at the place which includes several aspects of market and marketing. The results of the study show that the price offered by Centro is the cheapest price in Kajen District and has two adequate futsal courts so consumers can play without waiting long.